Determination of optimal timing of serial in‐utero transfusions in red‐cell alloimmunization. (November 2015) - Friszer, S.; Maisonneuve, E.; Macé, G.; Castaigne, V.; Cortey, A.; Mailloux, A.; Pernot, F.; Carbonne, B.
ABSTRACT: Objectives: To assess the performance of middle cerebral artery peak systolic velocity (MCA‐PSV) and of the expected daily decrease in fetal hemoglobin in determining the timing of serial in‐utero transfusions (IUT) in red‐cell alloimmunization. Methods: This was a retrospective study of a continuous series of suspected anemic fetuses undergoing IUT between June 2003 and December 2012. Doppler measurement of MCA‐PSV and pre‐ and post‐transfusion hemoglobin levels were recorded at the time of the first, second and third IUT. Receiver–operating characteristics (ROC) curves and negative and positive predictive values of MCA‐PSV in the prediction of severe fetal anemia were calculated. The daily decrease of fetal hemoglobin (Hb) between IUTs was calculated. Regression analysis was used to assess the correlation between pretransfusion fetal hemoglobin and MCA‐PSV, and between observed and expected (by projection of daily decreases) pretransfusion fetal hemoglobin levels. Results: One hundred and eleven fetuses required an IUT, of which 96 and 67 received a second and third IUT, respectively. The area under the ROC curve for MCA‐PSV in the prediction of severe fetal anemia was not different for each rank of transfusion. The positive predictive value of MCA‐PSV decreased from 75.3% at the first IUT, to 46.7% and 48.8% at the second and third IUTs, respectively, while the negative predictive value for a 1.5‐MoM threshold remained high (88.9% at the second and 91.7% at the third IUT). The mean daily decrease in hemoglobin following each transfusion was 0.45, 0.35 and 0.32 g/dL, respectively. There was a persistent linear correlation between fetal hemoglobin and MCA‐PSV and between observed and expected fetal hemoglobin levels. Conclusions: Both MCA‐PSV and projection of daily decrease in hemoglobin are reliable means of diagnosing fetal anemia following previous IUTs. The high negative predictive value of MCA‐PSV could allow subsequent IUTs to be postponed in selected cases. Copyright © 2014 ISUOG. Published by John Wiley & Sons Ltd.